Rainwater Treatment Using Treated Natural Zeolite and Activated Carbon Filter - Lili Mulyatna; Yonik M. Yustiani; Astri Hasbiah; Widya Yopita (UPT Penerbitan Universitas Jember, 2016)
Rainwater is an alternative sources of drinking water. The rainwater treatment process should be conducted before the rainwater can be consumed. One of the water treatment process is filtration. Zeolites and activated carbon are often used as filtration media due to its high availability and water pollutants removal efficiency. This research aims to measure filtration efficiency and the production cost of rainwater filtration treatment using modified/treated natural zeolite (TNZ) and activated carbon filter. Types of filter media used in this research are TNZ RC.32 (adsorbent for total dissolved solid, total suspended solid, CO2 and alkalinity), TNZ RC.42 (cation exchanger for Fe, Mn, color, and organic matter) and activated carbon filter. The research is conducted using four variations of filters configuration and two variations of reactor volume. The parameters tested are turbidity, total dissolved solid, pH, organic matter, and coliform. Reactor debit used is 0.01 l/sec. Filter configuration of TNZ RC.32 and activated carbon filter with 1.5 liter reactor volume has the highest organic substances removal efficiency by 58.85% and the lowest reactor production cost of Rp. 560,600. The results of rainwater treatment meets Indonesian drinking water regulation quality standards.